2014
DOI: 10.1186/1471-2164-15-716
|View full text |Cite
|
Sign up to set email alerts
|

Marked methylation changes in intestinal genes during the perinatal period of preterm neonates

Abstract: BackgroundThe serious feeding- and microbiota-associated intestinal disease, necrotizing enterocolitis (NEC), occurs mainly in infants born prematurely (5-10% of all newborns) and most frequently after formula-feeding. We hypothesized that changes in gene methylation is involved in the prenatal maturation of the intestine and its response to the first days of formula feeding, potentially leading to NEC in preterm pigs used as models for preterm infants.ResultsReduced Representation Bisulfite Sequencing (RRBS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
49
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 54 publications
7
49
0
Order By: Relevance
“…This finding supports the notion that pigs are a useful and stable biomedical model 12, 27 . In both pigs and humans, the hypothalamus-pituitary-ovary (HPO) axis is one of the key endocrine systems involved in the regulation of reproduction.…”
Section: Introductionsupporting
confidence: 89%
“…This finding supports the notion that pigs are a useful and stable biomedical model 12, 27 . In both pigs and humans, the hypothalamus-pituitary-ovary (HPO) axis is one of the key endocrine systems involved in the regulation of reproduction.…”
Section: Introductionsupporting
confidence: 89%
“…Our results show that the developmental expression of these enzymes is relatively independent of environmental factors, such as diet (which was the same for preterm and term pigs), and that intrinsic mechanisms related to ontogenetic age and genetic control could be more important. We recently documented that both preterm birth and enteral food introduction induce epigenetic effects on some immune-related genes in the immature pig intestine (19,53). It will be important to know whether preterm birth also induces epigenetic modifications to the sucrase-isomaltase and maltaseglucoamylase genes because this may help to explain why their corresponding enzyme activities were affected more long term whereas other gene functions tended to adapt more rapidly after preterm birth.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Relevant to preterm infants, at a molecular level, epigenetic processes constitute a major mechanism by which environmental factors may establish a new phenotypic trait during the plastic neonatal interval, 12,13 Recent studies have suggested that pre-and post-natal alterations to intestinal DNA methylation patterns contribute to high NEC susceptibility in preterm neonates. 14 An optimal early gut colonization may alter epigenetic signatures to establish inflammatory and barrier properties that protect against later insults that trigger NEC. It has also been shown that the epigenome of the host can be altered prior to exposure to early microbiota by gestational environmental exposures (e.g., nutrition, infection, drugs) or due to transgenerational inheritance.…”
Section: Introductionmentioning
confidence: 99%